Effectiveness of AM Fungi to Increase The Growth and Production of Peanuts Plant Infected by Sclerotium rolfsii - Swandi, Fradilla; Sulyanti, Eri; Darnetty, Darnetty (International Journal of Environment, Agriculture and Biotechnology, 2020)
Arbuscular Mycorrhizal Fungi (AM Fungi) are known to have the potential to increase plant growth. This study aims to find the best isolates of Indigenous Arbuscular Mycorrhizal Fungi (AM Fungi) that can increase the growth and production of peanuts plant infected by Sclerotium rolfsii caused stem rot disease. The method used is an experimental method with a Completely Randomized Design with 5 treatments, and 5 replication, namely A: AM Fungi Glomus sp-3 + S. rolfsii; B: AM Fungi Acaulospora sp + S. rolfsii; C: AM Fungi Gigaspora sp + S. rolfsii; D: Combined AM Fungi Glomus sp-3, Acaulospora sp, and Gigaspora sp + S. rolfsii; E: Without AM Fungi + S. rolfsii (Control). The data were analyzed using Analysis of Variance (ANOVA) using the Statistix 8 program and the Least Significance Different (LSD) test at a 5% significance level. The results showed that the Isolates of In general, Glomus sp-3 was able to increase the growth and production of peanuts.